A Potential Treatment of Congenital Sodium Diarrhea in Patients With Activating GUCY2C Mutations. Issue 11 (18th November 2021) - van Vugt, Anke H.M.; Bijvelds, Marcel J.C.; de Jonge, Hugo R.; Meijsen, Kelly F.; Restin, Tanja; Bryant, Manuel B.; Ballauff, Antje; Koot, Bart; Müller, Thomas; Houwen, Roderick H.J.; Janecke, Andreas R.; Middendorp, Sabine
Abstract : INTRODUCTION: Gain-of-function mutations in guanylyl cyclase C (GCC) result in persistent diarrhea with perinatal onset. We investigated a specific GCC inhibitor, SSP2518, for its potential to treat this disorder. METHODS: We investigated the effect of SSP2518 on GCC-mediated intracellular cyclic guanosine monophosphate (cGMP) levels and on GCC-mediated chloride secretion in intestinal organoids from 3 patients with distinct activating GCC mutations and from controls, with and without stimulation of GCC with heat-stable enterotoxin. RESULTS: Patient-derived organoids had significantly higher basal cGMP levels than control organoids, which were lowered by SSP2518 to levels found in control organoids. In addition, SSP2518 significantly reduced cGMP levels and chloride secretion in patient-derived and control organoids ( P < 0.05 for all comparisons) after heat-stable enterotoxin stimulation. DISCUSSION: We reported in this study that the GCC inhibitor SSP2518 normalizes cGMP levels in intestinal organoids derived from patients with GCC gain-of-function mutations and markedly reduces cystic fibrosis transmembrane conductance regulator–dependent chloride secretion, the driver of persistent diarrhea.